Tenants' experiences regarding satisfaction with existing complaint handling mechanisms in landlord managed apartments in Kampala - Mubiru, Moses; Naturinda, Comfort (Journal of Science and Technology, 2021)
This study assessed the tenants’ experiences regarding satisfaction with existing complaint handling mechanisms in landlord managed apartments in Najjera, Kampala City. The study employed a case study strategy and it was backed up with both qualitative and quantitative research approaches on a sample size of 91 respondents including tenants, landlords and landlords’ representatives. The data was collected with the help of questionnaires (25 tenants and 25 landlords), interviews (20 tenants and 15 landlords) and focus group discussion targeting 6 participants. analysis was through thematic categorisation, MS Excel and SPSS packages. This paper categorises tenant experiences regarding satisfaction with complaints handling mechanisms through complaints handling mechanisms used, modes of lodging complaints, duration of responses to complaints raised and timeliness of feedback mechanisms. Much as there was a notably high level of tenant satisfaction with apartment features, neighbourhood features and management factors, landlords address raised tenant issues and they ask for feedback from tenants to evaluate the effectiveness of the resolutions. There were obvious reservations among landlords regarding the legitimacy of complaints raised with lacking fairness, necessitating some complaints not to be attended to. This paper recommends efficient property management practices where landlords should adopt appropriate measures in order to improve and maintain their property in a habitable state through improving maintenance by engaging in planned maintenance programme; periodic and preventive maintenance schedules.
Keywords: Tenants’ Experiences; Satisfaction; Apartments